Vocal longevity phenomenon of the Latvian National opera soloist Karlis Zarins - Krīgere, Zigrīda (ARTS AND MUSIC IN CULTURAL DISCOURSE. Proceedings of the International Scientific and Practical Conference, 2014)
The focus of this paper is the analysis and research of the biographical factors that have influenced the longevity of the voice of opera soloist Karlis Zarins. The following materials have been used: singer biographies, partially structured interviews with K. Zarins and the doctor Dins Sumerags, internet resources, researches regarding factors influencing the voice, materials of vocal methodic, the personal stage experience and the observations from pedagogical practice of the author. It is concluded that the phenomenon of vocal longevity on stage relates to singers whose qualities of voice keep the characteristics of young and thriving voice – the freshness of timbre and endurance in an unusually long period of time, which considerably exceeds the statistical measurements of the average vocal ageing. The longevity of K. Zarins relates to four aspects: congenial physical and musical talents, the influence of social and natural surroundings, the creation of vocal competence during the studies and lifelong learning in professional, artistic and pedagogical areas. In this research, the components influencing K. Zarins phenomenon are observed.